Sequence analysis and homology modeling of coagulase in Staphylococcus aureus - Noor Asidah Mohamed
The production of extracellular substances by Staphylococcus aureus has been associated with the virulence and pathogenicity of these organisms for many years. Coagulase production is generally accepted as being characteristic of pathogenic and potentially pathogenic strains. Coagulase can cause clot formation in the immediate vicinity of the bacterium. In this study, the amino acid of coagulase in S. aureus remains that only one region was predicted for possible trans-membrane domains. Therefore, coagulase probably will be a soluble protein because it is hydrophilic. Corresponding with the fact, coagulase also predicted to localize in extracellular. Apart from that, the presence of signal peptide was predicted in this protein and the domain for this protein is the C-terminal tandem repeats which are not required for the procoagulant activity. Coagulase have derived a signature pattern specific for the 7 residue repeat of staphylocoagulase. Amino acid similarity comparison among other coagulase in S.aureus obtained from National Center for Biotechnology Information (NCBI) resulted high similarity as high as 99-100%. These prediction analyses demonstrated significant findings on the molecular similarity relationship between them. The similarities and deviation among the eight members would provide in deep idea documenting their functionality. Furthermore, the protein structure prediction of coagulase represented the model of coagulase by using homology approach. Through structural analysis inquiries concerning on the relationship between structure-function can be determined. Thus, structure predictions provide fundamental in understanding its native conformation hence the mechanism of the protein can fully be understood.